Write Your Own Luck Campaign: Pentel's Successful Advertising Strategy Based on Superstitious Beliefs in Thailand. (November 2021) - Chinchanachokchai, Punjaporn; Chinchanachokchai, Sydney
The Pentel case study exhibits a success case of a global firm's ability to incorporate cultural-specific values into an advertising campaign. Pentel used superstitious beliefs in the Thai culture to create the Write Your Own Luck campaign. The company launched a limited pen collection designed to be carried as lucky charms. Each pen version represented a unique type of luck it brought to its user. The campaign targeted Thai teens who were heavy users of social media. The campaign was launched through offline and online channels and received significant attention and awareness from the target audience. This case study represents a campaign that incorporates cultural beliefs and values of local consumers into an effective advertising campaign. The company achieved its goal of raising brand awareness and online engagement among the target audience.